Iron, zinc and total antioxidant capacity in different layers of rice grain among different varieties - Chanakan Prom-u-thai (2018)
© 2016 Friends Science Publishers. In addition to being an important source of iron (Fe) and zinc (Zn) for rice consumers, rice also has a special value in its anti-oxidative capacity. This study explored how antioxidant capacity of the rice grain is associated with its Fe and Zn concentration, and how the relationship is affected by milling. Total antioxidant capacity and the concentration of Fe and Zn were determined in 5 rice genotypes in unpolished grain and after polishing for 15, 30, 45 or 60 s. Total antioxidant capacity of the unpolished grain was positively correlated with its Zn concentration both determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging (r = 0.60, p < 0.05) and Fe reducing antioxidant power (FRAP) methods (r = 0.59, p < 0.05), while the correlation with its Fe concentration was found by FRAP method (r= 0.62, p < 0.05), suggesting an involvement of the nutrients in anti-oxidative activity. The concentration of Zn, Fe and total antioxidant capacity determined by DPPH method declined with longer polishing, while FRAP method was not detected the capacity after 15 s polishing. The total antioxidant capacity determined by DPPH method remained positively correlated with Zn concentration regardless of polishing time from 0 s to 60 s (r = 0.62, p < 0.001), but not with Fe (r = 0.12, not significant at p < 0.05) concentration. These results suggested a possible role of Zn in some oxygen radicals scavenging system that was constant through different layers of rice grain tissue, but the involvement of Fe was less clear.